LINGKUNGAN PENDIDIKAN DALAM ALQUR`AN: (Pengaruhnya dalam Proses Pendidikan) - Muhammad Anwar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2016)
Term of education milieu, explicitly, can not be found in Alqur`an, except it was existing in hostorical practice. In difference places that used as educational activities can appear defference influentials. If this fenomena was purposed, its sign was found in Alqur`an